PENGARUH SISTEM TANAM JAJAR LEGOWO DAN JARAK TANAM TERHADAP PERTUMBUHAN DAN HASIL PADI (Oryza sativa L.) CIHERANG - Turiono, Turiono; Zamroni, Zamroni; Pamungkas, Djoko Heru (JURNAL ILMIAH AGROUST, 2019)
This study discusses the interaction between planting with legowo jajar planting system on the growth and yield of rice plants. This study was arranged in a 3x2 factorial Complete Group Randomized Design (RAKL) with 3 replications. The first factor is the jajar legowo (J) plant system consisting of three initials, namely 2: 1 (J1), 4: 1 (J2), and 6: 1 (J3). The second factor is the spacing of 2 levels, namely the spacing of 20cm (P1) and spacing of 22cm (P2). The growth variables collected were tall plants, fresh heavy plants, number of tillers, number of productive tillers, weight of 1000 seeds, yield per hectare while the yield variable was the average plant height, mean of fresh plants, average number of tillers, average number of productive tillers, weight of 1000 seeds , average per hectare of all growth and yield variables. Data variables were analyzed with beginner's fingerprint error rate of 5% or average analyzed by DMRT at an error rate of 5%. The results of this study indicate that there was no interaction between legowo row treatments and spacing. However, the Jajar Legowo 2: 1 cropping system showed the best results on all research variables. Whereas the treatment of 20cm spacing shows the best results compared to the treatment of 22cm spacing